URINARY TRACT INFECTION WITH STUNTING AND NON-STUNTING IN RURAL AREA PANDEGLANG, BANTEN, INDONESIA 2021 - Wan Nedra; Yulia Suciati; Muhammad Arsyad; Sarah Kemalasari; Khansadhia Hasmaradana Moiindie; Mochamad Alif Ariesando; Nabila Wahyu Salsabilla; Adifa Mazdalifah (Medical Journal of Nusantara, 2023)
Urinary Tract Infections (UTIs) are bacterial infection that often occurs in childhood. Its occurrence depends on several predisposing factors and individual immunocompetence. Children with stunting have impaired immune function; therefore, early detection and prompt treatment of associated infections in children with stunting are critical. This study aimed to identify the association between UTI incidence in stunting and non-stunting children in Banten. This cross-sectional study was conducted in Pandeglang Regency, Banten. The subject of this study was 120 children aged 6 to 72 months. Well-nourished children matched for age were selected for the control group. Data was collected by a questionnaire-guided interview, physical examination, and urinalysis examination. Out of 120 respondents, 72 respondents (60%) were categorized as stunting and 26 respondents (21,67%) had UTIs. Out of the respondents who experienced UTIs, 15 respondents (12.5%) were categorized as severely stunted, and 5 respondents (4.17%) were categorized as stunted. There is an association between UTI and stunting.